INDUKSI KALUS DAN DETEKSI KANDUNGAN ALKALOID DAUN JARAK (Jatropha curcas L.) MENGGUNAKAN HORMON 2,4-D DALAM MEDIA MS (MURASHIGE SKOOG) - Yudi Rinanto (Universitas Trunojoyo Madura, 2011)
The research was conducted to examine 2,4-D hormone on callus induction and the synthesis of alkaloids in Jarak (Jatropha curcas L.) leaves callus on MS medium. The young leaves of Jarak are used as explant. The amount of 2,4-D hormone to be treated was 1 mg/l, 2 mg/l, dan 3 mg/l, respectively.Evaluation of callus formation was done after 8 weeks incubation time. Qualitative analysis on the Alkaloid was done by color reaction and by TLC (Tin Layer Chromatoghraphy) with stationary phase silica gel GF 254 and asetat:metanol:air (100:13,5:10) as movement phase. The chromatogram was observed under UV254 nm and UV366 nm lampsThe results showed 3 ppm concentration of 2,4-D hormone resulted highest growth of callus formation (85%), the fastest time of callus induction (12.2 days) and average weight (0.054 grams) of dried callus. SimakBaca secara fonetikThe qualitative analysis with Dragendorff reagent produced positive result brown color in TLC at UV254 nm, and blue color in UV366 nm. hRf value was almost the same as wild type. According to the research, alkaloid also found in the callus as in the wild type plant.